Determinants of Bone Mineral Density Changes in Women Transitioning to Menopause: A MONET Group Study - Elnefily, Rasha (Université d'Ottawa / University of Ottawa, 2013)
Menopause is an important period for bone health in women. Objective: To assess the determinants of bone mineral density (BMD) changes in women transitioning to menopause. Method: A secondary data analysis of the MONET (Montreal-Ottawa New Emerging Team) study. Outcome measures included yearly assessment of menopause status, body composition, BMD, physical activity energy expenditure (PAEE) and dietary calcium and vitamin D intakes. Results: 84 of the original 102 women had complete data for the purpose of the present study. Repeated measures analysis revealed significant decreases in lumbar spine and femoral neck BMD (P< 0.01). Regression analysis revealed that baseline femoral neck BMD, changes in PAEE and trunk fat explained 31% of the variation of BMD changes at the femoral neck, while changes in both PAEE and trunk fat account for 27% of BMD change at lumbar spine. Conclusion: Baseline femoral neck and changes in physical activity energy expenditure and trunk fat are determinants of the reduction of bone mineral density in women transitioning to menopause.
Keywords: Menopausal; bone mineral density; body composition; physical activity; dietary calcium; vitamin D